O impacto dos agrotóxicos nos peixes: parâmetros iniciais e efeitos persistente e transgeracional - Pompermaier, Aline (2022)
The presence of residues of emerging pollutants, such as pesticides, is a reality all over the world. Coming from different sources, such as direct application, leaching from crops or natural degradation processes, their effects on non-target species are still poorly understood. Zebrafish are an excellent model for ecotoxicological studies, as they have high prolificacy, translucent embryos, external fertilization and rapid development. The effects of fish contamination by environmental concentrations were evaluated by exposing embryos during the organogenesis period to the most widely used herbicides, glyphosate (GBH) and 2,4-D (DBH). We used environmental concentrations of 4.8 ug/L for glyphosate and 3.4 ug/L for 2,4-D. In our first paper, we evaluated the initial development parameters (mortality, hatching, spontaneous movement and heart rate), behavioral parameters (open field test and aversive stimulus) and also the possible mechanisms of action (SOD, CAT and AChE). In our second paper, we evaluated the persistent effects of exposure in adult animals through the new tank and aversive tests and then bred these animals to verify the transgenerational effects in the F1 generation, with the same analyses as in the F0 (initial development, behavioral parameters and biochemical biomarkers). In the F0 generation, exposure to glyphosate decreased survival, caused hypermobility and anxiolytic behavior, negatively affected the anti-predatory behavior of larvae and increased acetylcholinesterase activity, while exposure to 2,4-D caused only slight hypermobility in larvae and increased acetylcholinesterase activity. In the adult phase, fish exposed to GBH showed hypermobility and their anti-predatory response was impaired, characterizing a persistent effect. F1 larvae from fish exposed to GBH showed behavioral and survival changes, as well as effects on the activity of AChE and antioxidant enzymes, characterizing a transgenerational effect. As for DBH, the fish did not show persistent effects in the adult phase, however, they were unable to reproduce, which demonstrates that exposure affected the perpetuation of the species. These changes observed in all phases of the animals can compromise the perpetuation of the species, the search for partners/food and facilitate the action of predators, which can result in serious ecological imbalances and compromise the survival of the species.